2019
DOI: 10.1038/s41598-019-53623-2
|View full text |Cite
|
Sign up to set email alerts
|

A Plant Growth-Promoting Microbial Soil Amendment Dynamically Alters the Strawberry Root Bacterial Microbiome

Abstract: Despite growing interest in utilizing microbial-based methods for improving crop growth, much work still remains in elucidating how beneficial plant-microbe associations are established, and what role soil amendments play in shaping these interactions. Here, we describe a set of experiments that test the effect of a commercially available soil amendment, VESTA, on the soil and strawberry (Fragaria x ananassa Monterey) root bacterial microbiome. The bacterial communities of the soil, rhizosphere, and root from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 94 publications
7
45
0
1
Order By: Relevance
“…Indicator species (IS) and network analyses were used to identify at higher taxonomic resolution of the individual bacterial and/or archaeal species with enrichment or depletion patterns in different phases of anaerobic digestion. These analyses revealed the association of different methanogenic species with increased level of CH 4 production [61], and all were observed to be more abundant in highest CH 4 producing metagenome (Group-IV). However, common indicator bacteria E. coli , Salmonella and Staphylococcus species were not found in indicator species analysis, and these findings are supported by several previous reports of the absence of common indicator bacteria after 30 days digestion in the experimental AD at different temperatures (25 °C – 45 °C) [62].…”
Section: Discussionmentioning
confidence: 99%
“…Indicator species (IS) and network analyses were used to identify at higher taxonomic resolution of the individual bacterial and/or archaeal species with enrichment or depletion patterns in different phases of anaerobic digestion. These analyses revealed the association of different methanogenic species with increased level of CH 4 production [61], and all were observed to be more abundant in highest CH 4 producing metagenome (Group-IV). However, common indicator bacteria E. coli , Salmonella and Staphylococcus species were not found in indicator species analysis, and these findings are supported by several previous reports of the absence of common indicator bacteria after 30 days digestion in the experimental AD at different temperatures (25 °C – 45 °C) [62].…”
Section: Discussionmentioning
confidence: 99%
“…The combination of five biochar treatments was carried out in 10 replicates. Sample of 3 g was taken from each replicate to make carbofuran concentrations in the range of 2 to 20 mg/L (2,4,6,8,10,12,14,16,18,20 ). All these samples were thoroughly mixed and shaken for 24 hrs in an orbital shaker.…”
Section: Pot Trailsmentioning
confidence: 99%
“…The combination of five biochar treatments with carbofuran pesticide together was carried out in 10 replicates. The carbofuran concentrations were made in the range of 1 to 20 mg/L (2,4,6,8,10,12,14,16,18,20 ).All these samples were thoroughly mixed and shaken for 24 hrs in an orbital shaker till the equilibrium was achieved. An aliquot of 5 g of soil from each treatment was taken to determine the carbofuran concentration using UV/VIS spectrophotometer at 273 nm.…”
Section: Batch Sorption Processmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of PGPR is a possible alternative to reduce chemical inputs in agriculture (Etesami and Maheshwari 2018). Hence, exploration on the use of microorganisms to enhance soil fertility and plant nutrition continues to be interesting research topics reported by (Yan et al 2015;Pacheco-leyva et al 2016;Ahmad and Husain 2017;Patel et al 2017;Arfarita et al 2019;Deng et al 2019;Sheirdil et al 2019).…”
Section: Introductionmentioning
confidence: 99%